(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
Human trafficking in its most diverse forms is one of the criminal practices that historically takes us back to times when human beings were relegated to the status of mere objects or merchandise. In the 21st century, the practice of human trafficking is a regrettable repetition of historical events that have only been made invisible to the sometimes inattentive, sometimes blinded eyes of our society. From reading and analysing historical data, we can see that the processes of colonization in our country have their roots in people trafficking, in the case of black men and women from African countries, brought to Brazil as slaves to have their workforce exploited in order to generate wealth for their exploiters. The trade in human lives in our Brazilian reality is not something new. However, the approach and visibility, as well as the recognition of the issue in society, still fall short of the seriousness of the phenomenon.